Biodiesel Production from Waste Cooking Oil via Interesterification Reaction: Effects of Cajuput Oil Biocatalyst Concentration and Reaction Time - Briliant Saphira Wardhani; Malikha Syamsi; Elvianto Dwi Daryono; Jimmy Jimmy (G-Tech: Jurnal Teknologi Terapan, 2026)
Interesterification processes using homogeneous or heterogeneous catalysts generally require additional separation steps, reducing efficiency and increasing operational costs. Cajuput oil, whose main active compound is 1,8-cineole, contains aromatic functional groups that show potential as a biocatalyst and can be applied without a separation step at the end of the reaction, thereby improving process efficiency. This study aims to determine the optimum conditions for the interesterification of waste cooking oil based on cajuput oil biocatalyst concentration and reaction time. Waste cooking oil, methyl acetate, and cajuput oil biocatalyst at concentrations of 0.5–1.5% were reacted in a two-neck round-bottom flask reactor at 60°C, a stirring speed of 300 rpm, an oil-to-methyl acetate molar ratio of 1:6, and reaction times ranging from 20 to 100 min. After the reaction, unreacted methyl acetate was removed by distillation, and the residue was characterized as the final product. The optimum conditions were achieved at a biocatalyst concentration of 1% and a reaction time of 60 min, producing a crude yield of 78.80%, an acid value of 0.45 mg KOH/g, a density of 0.88 g/mL, and a viscosity of 2.94 cSt, which comply with SNI 7182:2015, along with a FAME concentration of 19,406.50 mg/L. The novelty of this research lies in the biodiesel production process that eliminates the separation of the by-product triacetin and the cajuput oil biocatalyst, as both function as bio-additives in the biodiesel. Consequently, the process becomes simpler and more efficient, without requiring lengthy or complex processing steps.